Perwujudan Keharmonisan Hubungan antara Manusia dengan Alam Dalam Upacara Hindu di Bali - Budiasih, Ni Made (Institut Hindu Dharma Denpasar, 2019)
Living things come from food. Food comes from plants. Plants come from rain. Rain comes from YADnya. Yadnya it is karma. Without plants, all living beings cannot carry on their lives, because the basic ingredients of animal and human food are plants. The existence of plants is yadnya from earth and sky to all living things. The teachings of Hinduism include three frameworks, namely tattwa, etika and upacara. In its implementation implemented Hindus in an integrated and intact. But in reality the more prominent part is the ceremonial part. This is because this part is a form of implementation with all its accessories. The big day is Tumpek wariga, also known as bubuh tump, pengatag tump, steering tump. It falls on the day of Saniscara, Kliwon, Wuku Wariga, or 25 days before Galungan. A series of ceremonies and ngatagin ceremonies were held to worship Bhatara Sangkara, the manifestation of Hyang Widhi, invoking the fertility of plants that are useful for human life. Bentuyung), Lord of Plants Plants that are concrete through treating the trees by offering porridge. In addition, Tumpek wariga is also an initial series in preparation for the Galungan holiday. In addition, the Ngerasakin Â Ceremony is a ceremony that aims to express gratitude to Ida Sang Hyang Widhi Wasa with manifestations as Jero Sedahan Abian and Jero Sedahan Sawah for what has been enjoyed so far from the produce of the earth.